Effectiveness of Sembako Program Management for Poor Beneficiary Families (KPM) (Case Study in Banyumanik District of Semarang City) - Munawar Noor (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research aims to describe and analyze the effectiveness of Sembako program management in improving the welfare of KPM in Banyumanik District of Semarang City. The type of research used in this research is descriptive research with a qualitative approach. Informants in this study include: Social Companion of Bansos Pangan Banyumanik Subdistrict, e-Warong Administrator, Banyumanik Subdistrict Social Welfare Kasie and Family Beneficiaries of Sembako program. The conclusion of the study that all stages of the program aspects of management (planning, organizing, commanding, controlling and coordinating), there are weaknesses such as taking KKS mustinya KPM but often represented by the village, there is a KKS that is no longer active, e-warung owners sell higher prices. From the aspect of effectiveness (punctuality, goal accuracy and the accuracy of the program's objectives) have not been effective, it still occurs for example too many are involved, especially in the aspect of edication and socialization, taking KKS must be KPM but often represented by the village,. The existence of KPM that is no longer active, higher prices in e-warung burden the target program. Recommendation: Sembako program for poor beneficiaries (KPM) greatly helps the poor to improve welfare by improving weaknesses from management aspects and effectiveness. It is necessary to develop a sembako program model that is simple, understandable and can be implemented by poor people target programs.